2012
DOI: 10.2298/vsp1210904b
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of thermovision application in sport and sport rehabilitation

Abstract: Thermovision is fast and efficient in detecting different kind of injuries, so its increased use in the future can be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 4 publications
0
12
0
2
Order By: Relevance
“…In contrast, the surface body temperature ranges from 36.2 to 37.8°C and depends on a segment of the body. Any form of physical activity increases tissue metabolism, which accelerates oxygen transport due to increased blood flow leading to elevation of body temperature caused by heat production by working muscles [24,25]. In case of professional sport, the increase in capability of heat removal from the body is important (limitation of increase in inner temperature and dynamics acceleration of sweat secretion) which as a consequence allows for continuation of exercise [25].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the surface body temperature ranges from 36.2 to 37.8°C and depends on a segment of the body. Any form of physical activity increases tissue metabolism, which accelerates oxygen transport due to increased blood flow leading to elevation of body temperature caused by heat production by working muscles [24,25]. In case of professional sport, the increase in capability of heat removal from the body is important (limitation of increase in inner temperature and dynamics acceleration of sweat secretion) which as a consequence allows for continuation of exercise [25].…”
Section: Discussionmentioning
confidence: 99%
“…[910111213141516171819] Holey et al reported, recently, that skin temperature showed significant increases immediately after connective tissue massage. [9] It is interesting that manual treatment can also induce significant temperature elevations in nonmassaged areas.…”
Section: Discussionmentioning
confidence: 99%
“…[17] In 1994, Walko and Janouschek used thermographic analysis in clinical osteopathic research. [18] Today, infrared thermography is increasingly applicable in sport and sport rehabilitation[19] It is a method that can be easily applied, and is fast and efficient in detecting different kinds of injuries[19] Therefore one can expect its increased use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of these changes by means of thermography can provide information about how quickly the body returns to thermal homeostasis after physical exertion by mapping body heat production in the wake of physical exertion. Thermography can also be used in the prevention of injuries and controlling the progression of motor features [11,12].…”
Section: Introductionmentioning
confidence: 99%